The current situation of female scientists in Argentina - Llois, A.M. (2009)
We report the changes that have taken place recently regarding the situation of female scientists in Argentina. We comment on the rules for maternity leave that have been passed recently for research scholars doing their PhDs and on the number of women scientists that occupy decision making-positions in science. We also present some evidence that seems to indicate that, among young scientists, women are more willing to occupy leadership positions and that the Argentinean society is more accepting of this new role. © 2009 American Institute of Physics.